Typology of the Peri-Urban Area in Demak District - Pigawati, Bitta; Ghaisani, Shabrina (Semarang State University, 2020)
Abstract. The increase in population has an impact on increasing the demand for land. In addition, the available land in the city is relatively limited. Therefore, the development leads to the peri-urban area. The development of the core city will have an impact on the physical, social, and economic transformation of the peri-urban area. Interactions that occur between rural-urban areas can affect the development of peri-urban areas. Interaction between rural-urban areas also occurs in Mranggen Sub – district as the peri – urban area of Semarang. This study aims to examine changes in the typology of peri-urban areas in Mranggen Sub – district, Demak District in 2008 - 2018. This research used a quantitative descriptive method with a spatial approach. The remote sensing data were used as the main data source and document review as secondary data. The change in the typology of Potential Urban to Semi Urban was caused by changes in people's livelihoods, increased education, percentage of permanent buildings, educational facilities, and health facilities. The change in typology from Semi Urban to Predominantly Urban is caused by various variables that cause increasingly urbanization. The results showed a change in the study area, 7 villages changed from the typology of Potential Urban to Semi Urban and 2 villages changed from the Semi Urban typology to Predominantly Urban.